Some Geometric Properties of Generalized Class of Meromorphic Functionsassocisted with Higher Ruscheweyh Derivatives - Jassim, Kassim Abdul Hameed; Hussein, Adnan Aziz (Iraqi Journal of Science, 2019)
The applications of Ruscheweyh derivative are studied and discussed of class of meromorphic multivalent application. We get some interesting geometric properties, such as coefficient bound, Convex linear combination, growth and distortion bounds, radii of starlikenss , convexity and neighborhood property.